Identification and Functional Characterization of a Novel Nonsense Variant in ARR3 in a Southern Chinese Family With High Myopia - Yuan, Dejian; Yan, Tizhen; Luo, Shiqiang; Huang, Jun; Tan, Jianqiang; Zhang, Jianping; Zhang, Victor Wei; Lan, Yueyuan; Hu, Taobo; Guo, Jing; Huang, Mingwei; Zeng, Dingyuan (Frontiers in Genetics, 2021)
Only four (likely) pathogenic ARR3 mutations have been reported worldwide. ARR3 has been associated with X-linked, female-limited, high myopia. However, using exome sequencing (ES) in a Southern Chinese family, we identified the first high myopia case with hemizygous ARR3-related mutation in a male patient. This novel truncated mutation (ARR3: c.569C>G, p.S190*) co-segregated with the disease phenotype in affected family members, and demonstrated that high myopia caused by ARR3 is not X-linked, female-limited, where a complicated X-linked inheritance pattern may exist. Thus, our case expanded the variant spectrum in ARR3 and provided additional information for genetic counseling, prenatal testing and diagnosis. Moreover, we characterized the nonsense-mediated decay of the ARR3 mutant mRNA and discussed the possible underlying pathogenic mechanisms.